Universidad pública, abierta y gratuita: Análisis de factores cruciales para la evaluación de esta popítica pública - Pablo D. López Zadicoff (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2006)
– The main argument supporting the policy of public, gratuitous and universal university is the one of equalization of opportunities. Nevertheless, the debate usually omits two crucial issues: the sequential characteristic of the educative process, and the opportunity cost of its financing. This paper develops a theoretical model that acknowledges these factors, concluding that public university can be a sub-optimal redistributive policy. Moreover it presents an empirical analysis, based on probit-type regressions, which show that the probability of benefiting from public university increases significantly with the agents' income.
Keywords: I2; H5; 330; Hochschulpolitik; Argentinien